Novel metabolic disorders in skeletal muscle of Lipodystrophic Bscl2/Seipin deficient mice. (15th February 2019) - Xu, Wenqiong; Zhou, Hongyi; Xuan, Hongzhuan; Saha, Pradip; Wang, Gongxian; Chen, Weiqin
Abstract: Bscl2 −/− mice recapitulate many of the major metabolic manifestations in Berardinelli-Seip congenital lipodystrophy type 2 (BSCL2) individuals, including lipodystrophy, hepatosteatosis, muscular hypertrophy, and insulin resistance. Metabolic defects in Bscl2 −/− mice with regard to glucose and lipid metabolism in skeletal muscle have never been investigated. Here, we identified Bscl2 −/− mice displayed reduced intramyocellular triglyceride (IMTG) content but increased glycogen storage predominantly in oxidative type I soleus muscle (SM). These changes were associated with increased incomplete fatty acid oxidation and glycogen synthesis. Interestingly, SM in Bscl2 −/− mice demonstrated a fasting duration induced insulin sensitivity which was further confirmed by hyperinsulinemic-euglycemic clamp in SM of overnight fasted Bscl2 −/− mice but reversed by raising circulating NEFA levels through intralipid infusion. Furthermore, mice with skeletal muscle-specific inactivation of BSCL2 manifested no changes in muscle deposition of lipids and glycogen, suggesting BSCL2 does not play a cell-autonomous role in muscle lipid and glucose homeostasis. Our study uncovers a novel link between muscle metabolic defects and insulin resistance, and underscores an important role of circulating NEFA in regulating oxidative muscle insulin signaling in BSCL2 lipodystrophy. Highlights: Bscl2 −/− mice display reduced triglyceride but increased glycogen storage in skeletal muscle. Fatty acid oxidation in oxidative soleus muscle of fed Bscl2 −/− mice is enhanced. Prolonged fasting sensitizes insulin sensitivity in oxidative soleus muscle of Bscl2 −/− mice. Intralipid infusion mitigates muscle insulin sensitivity in Bscl2 −/− mice after a prolonged fasting. BSCL2 does not play a cell-autonomous role in skeletal muscle triglyceride and glycogen metabolism.